Forever and always - Thurman, Brittany (Greenwillow Books, an imprint of HarperCollinsPublishers, 2024)
Exploring the day-to-day life of a young Black child and her family, this lyrical picture book centers around Olivia, who, worrying about her father while he's at work, anxiously awaits his return, knowing that when he gets home, the evening will be full of love and fun.